Special C&G session at EuroVis 2022. (October 2022) - Isenberg, Tobias; Bruckner, Stefan
Abstract: The authors of a selection of visualization-related articles from Computers & Graphics presented their work in a special at this year's EuroVis conference. This was the second edition of this special session at EuroVis, whose goal is to give the authors of pure journal articles a better visibility of their work.